Generation Y in the family succession of small businesses in São Paulo (Research, Society and Development, 2022)
The most likely successors of today's family businesses – the young people from Generation Y, which includes those born between 1982 and the year 2000 – have several specificities in their way of seeing and experiencing the world, which are directly affected by the context. current cultural and socioeconomic. The objective of this work was to analyze the challenges of Generation Y in the family succession process of micro and small companies located in the metropolitan region of São Paulo. The methodology used was an exploratory, qualitative case study of ten family businesses that have gone through or will go through the succession process involving young people from Generation Y. The analysis of the material, in turn, was anchored in the methodology of Analysis of Content by the author Bardin (1997) and in the qualitative material analysis software NVIVO. The results showed that the succession process in MSEs presents challenges that include the lack of preparation of successors, lack of motivation and the emergence of family conflicts directly influenced by the absence of a previously outlined strategic plan.